Pertanggungjawaban Pidana Pegawai Bank BUMN atas Penyalahgunaan Wewenang Fungsional - Afifah Vilania Putri; Hafrida; Elizabeth Siregar (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This article examines the uncertain boundary between contractual authority held by employees of state-owned banks and the abuse-of-authority element under Article 3 of the Corruption Law. It focuses on Jambi District Court Decision Number 36/Pid.Sus-TPK/2025/PN Jmb concerning manipulated documents for People’s Business Credit (KUR) financing at PT Bank Syariah Indonesia Tbk. This normative legal study applies statutory, conceptual, and case approaches. Primary legal materials are examined through grammatical, systematic, and teleological interpretation and through reconstruction of the ratio decidendi of the trial and appellate decisions. The study finds that the courts’ reliance on Article 2 paragraph (1), rather than Article 3, is doctrinally defensible because Article 2 paragraph (1) does not require proof that the defendant’s authority originated in public law. Liability nevertheless requires proof of an unlawful act, enrichment, culpability, causation, and actual state financial loss. Constitutional Court Decisions Number 48/PUU-XI/2013 and Number 62/PUU-XI/2013 confirm that separated state capital remains within state finances, while business management must still be assessed under business-judgment principles. The novelty of this article is a four-stage qualification test covering the source of authority, the status and actuality of loss, culpability and causal connection, and selection of the appropriate criminal-law regime. This test offers a more precise basis for distinguishing corruption from contractual breaches, banking offences, and ordinary crimes.